Monitoring of ph, redox and turbidity in a water treatment plant using WSN with ZIGBEE technology - Fonseca-Gonzaléz, Gerson; Avendaño, Eduardo; Araque, Andrés Leonardo (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2014)
This paper presents the design of a WSN using Zigbee technology (Standart IEEE 802.15.4), With the help of the XBee of Maxtream modules the communication is carried out between a remote water treatment plant towards a ccordinator node. The acqired data are entered to a microcontroller which takes care of the processing to be able to transmit and visualized under a graphical user interface in Matlab